INVESTIGATION OF THE SIMILARITY OF LAND SELECTED FOR AREA-YIELD CROP INSURANCE FOR THAI RICE - Duangmanee, Krittiya; Fransen, Erik (European Scientific Journal, ESJ, 2013)
Thailand has the fifth biggest harvested area of rice of any of the countries in the world. Rice growing is principally dependent on weather-related factors and the number of natural disasters appears to have been rising year after year, exerting a highly significant impact on Thai farmers. This study aims to investigate a potential risk mitigation approach for major rice insurance to protect their interests, namely the area-yield index, in which the first vital step is the selection of the area in order to reduce basis risk. The similarity between the various areas of land chosen is investigated and historical data covering the years 1995-2011 for crop rice from six provinces in the northeast of Thailand - LOEI, NAKHONPHANOM, NONGBUALAMPHU, NONGKHAI, SAKONNAKHON and UDONTHANI - are assessed. The results show that on the basis of the relevant variables examined, there are differences between the provinces in terms of both area and climate.